2002
DOI: 10.1159/000058009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary <i>Helicobacter pylori</i> Resistance to Several Antimicrobials in a Saudi Teaching Hospital

Abstract: Objective: To determine the resistance rate of the most commonly used antimicrobial agents amongst Helicobacter pylori isolates. Methods: The agar disk diffusion method (Kirby Bauer) was utilized to determine the susceptibility of 223 H. pylori strains isolated before treatment. Isolates were tested against metronidazole (5 µg), clarithromycin (15 µg), amoxycillin (10 µg), and tetracycline (30 µg). Results: The resistance rate was 80% for metronidazole and 4% for clarithromycin. Tetracycline and amoxycillin sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
4
14
1
Order By: Relevance
“…However, we observed no resistance to TCN, consistent with reports from other countries [35][36][37][38], but in contrast to studies from India and Pakistan [39][40][41]. This difference may in part be attributed to different usage of this antibiotic in various countries.…”
Section: Discussionsupporting
confidence: 90%
“…However, we observed no resistance to TCN, consistent with reports from other countries [35][36][37][38], but in contrast to studies from India and Pakistan [39][40][41]. This difference may in part be attributed to different usage of this antibiotic in various countries.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 56.3% of the H. pylori isolates were resistant to metronidazole, which was lower than the results obtained by Mohammadi et al (18). The rate of metronidazole resistance in Saudi Arabia (15) and China (17) was close to our study, which could be due to the regional distribution of resistance to antibiotics. The rate of resistance to tetracycline was around 15.6% in our study, while the rate of resistance to this antibiotic was no more than 5% in Italy (19), Saudi Arabia (15) and South Korea (16).…”
Section: Resultssupporting
confidence: 83%
“…The rate of metronidazole resistance in Saudi Arabia (15) and China (17) was close to our study, which could be due to the regional distribution of resistance to antibiotics. The rate of resistance to tetracycline was around 15.6% in our study, while the rate of resistance to this antibiotic was no more than 5% in Italy (19), Saudi Arabia (15) and South Korea (16). However, the rate of tetracycline resistance has been reported to be up to 50% in China (17).…”
Section: Resultssupporting
confidence: 83%
“…In Iran, the resistance rate has been increasing, from 33% in 1997 to 76.8% in 2012 [13,14,[41][42][43][44]58] . The rate has also been rising from 38% to 78.5% over the past 20 years in Saudi Arabia [59][60][61][62] . Moreover, in 2 different studies, 42.6% and 63% of H. pylori strains were resistant to Metronidazole in 2012 in Turkey and United Arabia Emirates, respectively [63,64] .…”
Section: Therapymentioning
confidence: 99%
“…But when administering higher doses, some studies have reported optimal results even in case of high resistance to Metronidazole. Luther et al [66] reported 97.1% PP eradication rate with 2 wk of Omeprazole (20 mg BD), Bismuth sub- Iran [13] 1997-2000 70 DDM 1.4 33% 0% 1.4% Iran [14] 2001-2004 135 DDM 3.7 36.3% 0.7% 3.7% Iran [42] 2005 120 DDM 1.6 57.5% 0% 16.7% Iran [58] 2005 [110] 2013 153 DDM 7.2 63.8% -26.5% -Turkey [45] 2003 87 DDM ---27.5% Turkey [16] 2004 110 DDM ---48.2% Turkey [17] 2006 92 DDM ---40.5% Turkey [111] 2007 61 DDM ---16.4% Turkey [63] 2012 61 DDM 0 42.6% 0% 21.3% Levofloxain: 3.3% Lebanon [112] 2002 54 DDM 0 29.5% 2% 4% Bahrain [15] 1999 83 Epsilometer test -57% -33% Saudi Arabia [59,61] 1988 71 DDM -38% 1.4% -Saudi Arabia [59,61] 1996 62 DDM -85.5% 0% -Saudi Arabia [59] 1998 63 DDM -78.5% --Saudi Arabia [60] 2002 223 DDM 1.3 80% 0.4% 4% Saudi Arabia [62] 2008 46 DDM 0 69.5% -21% UAE [113] 2010 26 E-test ---19.2% UAE [64] 2013 16 ? -63% --Syria [114] 2012 ously during the entire duration of therapy.…”
Section: Therapymentioning
confidence: 99%